Sodium butyrate and sodium propionate inhibit breast cancer cell migration and invasion through regulation of epithelial-to-mesenchymal transition and suppression of MEK/ERK signaling pathway - Kharazi, Dania Mahmoud; Karam, Louna; El Boustany, Charbel; Ibrahim, José-Noel (Frontiers in Cell and Developmental Biology, 2025)
ObjectiveThis study aims to investigate the roles played by NaB and NaP in breast carcinogenesis by elucidating their potential anti-metastatic effects in the context of tumor migration, invasion, and EMT regulation in two distinct breast cancer cell lines, MCF-7 and MDA-MB-231.MethodsThe cytotoxic effect of both compounds on 3D spheroid formation was evaluated using a hanging drop assay. The anti-migratory and anti-invasive potentials of NaB and NaP were investigated through transwell migration and invasion assays. Moreover, their role in regulating epithelial-to-mesenchymal transition (EMT) was examined by assessing E-cadherin, vimentin, and β-catenin mRNA and protein expression levels through RT-qPCR and Western blot or flow cytometry. β-Catenin localization upon treatment was further visualized via immunofluorescence. Protein expression of MEK, p-MEK, ERK, and p-ERK was analyzed by Western blot.ResultsOur results revealed a dose- and time-dependent impairment of spheroid formation in both cell lines, with NaB exerting a more potent effect than NaP. Both SCFAs were able to significantly inhibit migration and invasion of MDA-MB-231 cells following 24 h of treatment. Moreover, treatment with NaB or NaP altered the mRNA and protein profile of EMT-associated markers and abrogated the nuclear translocation of β-catenin. Finally, ERK and MEK phosphorylation was reduced in MDA-MB-231 and MCF-7 cells upon treatment with NaB, and less prominently with NaP.ConclusionOur study highlights the promising therapeutic potential of NaB and NaP, providing insight into their inhibitory effects on 3D formation, migration, and invasion through EMT regulation and deactivation of MEK/ERK signaling in breast cancer.